AN ANALYSIS OF METAPHOR IN PEOPLE MAGAZINE'S ADVERTISEMENT - Triartha, Fenti -; Ginting, Siti Aisah (Universitas Negeri Medan, 2014)
This study aims to find out the effect of applying community language learning method on the students™ achievement in speaking. The population of the study was the first year student at Man 2 Model Medan. In this study the sample is 50 students where 25 students took as experimental group and 25 students rest was control group. The data of this study was collected by oral test . It was applied in pre test and post test, then the scores were analyzes by using t-test formula. The result of the analysis showed that t-observed value is higher than t-table value ( 3>2.00 ) at the level os significant 0.05 with the degree of freedom 48. It means that there was a effect of applying community language learning method on the students™ achievement in speaking. Keywords: Community Language Learning, Students™ Achievement, Speaking